Duration of the runaway electron beam at a subnanosecond leading edge of the voltage pulse - Tarasenko, Viktor Fedotovich (Technical physics)
The conditions have been studied, under which, during a subnanosecond breakdown of centimeter-length gaps filled with air at atmospheric pressure, current pulses of a runaway electron beam (RAEB) of a minimum duration are recorded. It is shown that the duration of the RAEB current pulse depends on many parameters, including the shape of the cathode, the length of the interelectrode gap, the diameter of the diaphragm, which is a part of the anode, and the size of the receiving part of the collector. It has been established that with the use of cathodes with an extended edge having a small radius of curvature, with small aperture diameters in the anode, RAEB consisting of two peaks of picosecond duration can be recorded.